Students as surrogates for managers: Evidence from a replicated experiment. (25th April 2016) - Trottier, Kim; Gordon, Irene M.
Abstract: Using students as surrogates for managers in experiments is commonplace, yet the validity of this practice has not been fully established. To explore the appropriateness of using student samples, we replicate an experiment previously conducted employing a sample of senior managers involved in financial reporting. The result is that although student and manager responses are significantly different from a statistical perspective, both samples lead to the same conclusion for this experiment. The findings suggest that having some disassociation between students and the target population they are meant to represent does not necessarily make them inappropriate surrogates. To examine when inferences are best supported, we explore the comparability for student subgroups and managers along dimensions of experience, knowledge, culture, and gender. Copyright © 2016 ASAC. Published by John Wiley & Sons, Ltd.